Evidence-Based Analysis Of Basic Volleyball Training Methods: Focus On Overhand Serves And Underhand Passes - Marta Aurelia Sitorus; Dwi Reva Nita Sela Br Tarigan; Erike Wanate Mahara; Delon Steven Bintang; Lewi Nababan; Deni Rahman Marpaung; Randi Kurniawan (STAMINA, 2025)
This study analyzes the effectiveness of various volleyball basic technique training methods, focusing on overhead serves and underhand passes, through an evidence-based approach. This study was conducted to address the need for more adaptive technical training to meet the demands of modern play, given that conventional training approaches, which tend to be repetitive, still dominate and often fail to improve skill transfer to game situations. The analysis was conducted on a number of studies that highlighted variations in training methods, such as blocked practice, random practice, mixed practice, paired drills, small-sided games, and the use of mechanical and visual feedback. The main findings show that blocked practice is effective in the early stages of movement pattern formation, while random and game-based practice is superior in skill transfer and long-term retention. Partner drills are more effective at improving groundstrokes than individual practice, while mechanical feedback has been shown to be more accurate in improving the kinematic consistency of overhead serves than verbal instruction. This study confirms that the most effective training approach is the integration of stabilization of basic movement patterns, variation in training conditions, game context, and data-based technical feedback. The results of this study can be used as a reference for coaches, sports educators, and practitioners to design training programs that are scientific, applicable, and relevant to the characteristics of modern volleyball